RARE-20. MALIGNANT PERIPHERAL NERVE SHEATH TUMOR OF A CRANIAL NERVE IN AN INFANT WITH NEUROCUTANEOUS MELANOSIS. (4th December 2020) - Carter, Lacey; Gross, Naina; McNall-Knapp, Rene; Peterson, , and Jo Elle
Abstract: At one month of age, a female presented with a giant congenital nevus along lower back and thighs and hydrocephalus. A ventriculoperitoneal shunt was placed. An MRI was done at six months, initially reported as normal. At eleven months of age, five months after original MRI, patient presented with dysconjugate gaze and lethargy. MRI showed new 3.8 x 3.7 x 3.4 cm right cerebellopontine angle mass extending into Meckel's cave and foramen ovale along with leptomeningeal disease extending from the mass along the entire length of the spinal cord. Retrospective review of prior MRI revealed subtle leptomeningeal enhancement concerning for neurocutaneous melanosis (NCM). Given the leptomeningeal disease, family elected for open biopsy and debulking of lesion instead of aggressive resection. Histologically, the mass showed hypercellular spindle cell neoplasm with mitotic activity and necrosis mixed with remnants of normal cranial nerve. GFAP was negative, excluding a glioma. HMB-45, MITF, panmelanoma, and Melan-A were negative, excluding melanoma. A negative myogenin stain ruled out ectomesenchymoma. S-100 protein and SOX-10 positivity with variable loss of staining for trimethylation of histone H3 K27 were indicative of malignant peripheral nerve sheath tumor (MPNST). Given the course of the mass, trigeminal nerve MPNST was presumed. Given the poor prognosis of intracranial MPNST and NCM, family elected to forgo treatment and was discharged with hospice. She died 25 days after surgery. Cranial nerve MPNST is rare. MPNST in patients with NCM has not previously been reported to our knowledge.